Functional copolymers of p-cumyl phenyl methacrylate and glycidyl methacrylate: synthesis, characterization, and reactivity ratios - Ratnaprabha, K.; Daliya, P. K. (Journal Applied Polymer Science, 2005)
Free-radical polymerization of p-cumyl phenyl methacrylate (CPMA) was performed in benzene using bezoyl peroxide as an initiator at 80&DEG; C. The effect of time on the molecular weight was studied. Functional copolymers of CPMA and glycidyl methacrylate (GMA) with different feed ratios were synthesized by free-radical polymerization in methyl ethyl ketone at 70&DEG; C, and they were characterized by FTIR and H-1-NMR spectroscopy. The molecular weights and polydispersity indexes of the polymers and copolymers were determined by gel permeation chromatography. The copolymer composition was determined by H-1-NMR. The glass-transition temperature of the polymer and the copolymers was determined by differential scanning calorimetry. The reactivity ratios of the monomers were determined by the Fineman-Ross and Kelen-Tudos methods. © 2005 Wiley Periodicals, Inc.
Keywords: copolymerization; functionalization of polymers; glass-transition; synthesis

Improved synthesis of an energetic material, 1,3,3-trinitroazetidine (TNAZ) exploiting 2-iodoxy benzoic acid (IBX) as an oxidising agent - Singh, A; Sikder, N; Sikder, AK (Indian Journal of Chemistry Section B - Organic Chemistry including Medicinal Chemistry, 2005)
Tetrahydropyranyl protected 1,3-dihalo-2-propanol reacts with p-toluene sulfonamide in the presence of K2CO3 to give corresponding N-p-tosyl-3-azetidinol. Deprotection and oxidation with iodoxy benzoic acid followed by oximation of N-p-tosyl-3-azetidinone readily affords the corresponding azetidine oxime in almost quantitative yield. The subsequent oxidative nitrolysis of oxime gives 1,3,3-trinitroazetidine (TNAZ) through a new sequence of reactions with excellent purity (> 99%) and moderate yield (40%).
Keywords: 2-iodoxy benzoic acid; insensiive munitions; oxidative nitrolysis; oximination; strained ring; synthesis; trinitroazetidine

Synthesis and biodegradability of polyaspartic acid: a critical review - Thombre, SM; Sarwade, BD (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
Poly(aspartic acid) (PAA) being biodegradable is suitable for various industrial medical and agricultural applications to replace many non-biodegradable polymers in use. Poly(aspartic acid) can be synthesized by different methods with and without catalyst in different forms such as polysuccinimide, either hydrolyzed to acid or salt. The polymer of (aspartic acid) is present in different forms such as alpha, beta and L, D isomers. The conformational analysis of poly(aspartic acid) was done by various analytical methods. Different combinations of these two isomer present in different percentage can be detected by various methods such as Hoffman degradation, IR, and NMR spectroscopic analysis. From the standard test for biodegrad ability, it was shown that the polymer is fully biodegradable. In this review, synthesis and characterization of homo and copolymer derivatives of PAA, along with the application and biodegradability in comparison with the other polymer in use, is discussed briefly.
Keywords: Biodegradation; poly(aspartic acid); Polycondensation; polysuccinimide; synthesis; thermal

Synthesis of naturally occurring bioactive butyrolactones: maculalactones A-C and nostoclide I - Kar, Anirban; Gogoi, Sanjib; N. P. Argade (Tetrahedron, 2005)
Starting from citraconic anhydride (13), a simple multistep (9-10 steps) synthesis of naturally occurring butyrolactones maculalactone A (3), maculalactone B (1), maculalactone C (2) and nostoclide 1 (4) have been described with good overall yields via dibenzylmaleic anhydride (20) and benzylisopropylmaleic anhydride (27). The two anhydrides 20 and 27 were prepared by S(N)2' coupling reactions of appropriate Grignard reagents with dimethyl bromomethylfumarate (14), LiOH-induced hydrolysis of esters to acids, bromination of carbon-carbon double bond, in situ dehydration followed by dehydrobromination and chemoselective allylic substitution of bromoatom in disubstituted anhydrides 19 and 26 with appropriate Grignard reagents. The NaBH4 reduction of these anhydrides 20 and 27 furnished the desired lactones 21 and 29, respectively. The lactone 21 on Knoevenagel condensation with benzaldehyde, furnished maculalactone B (1), which on isomerization gave maculalactone C (2). Selective catalytic hydrogenation of 1 gave maculalactone A (3). The conversion of lactone 29 to nostoclide 1 (4) is known. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: dimethyl bromomethylfumarate; disubstituted maleic anhydrides; maculalactone A-C; NaBH4 reductions; nostoclide 1; S(N)2 ` Grignard couplings; synthesis

Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

Chemistry of recently isolated naturally occurring quinazolinone alkaloids - Mhaske, Santosh B.; N. P. Argade (Tetrahedron, 2006)
The present review portrays a concise account of the isolation, bioactivity, and synthesis of bioactive quinazolinone-based natural products for the period 1983-2005 and the recent developments in the area of complex quinazolinone natural products with a special emphasis on new synthetic routes and strategies. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1983-2005; bioactivity; concise account; isolation; natural quinazolinones; synthesis

Effect of organic additives on the mitigation of volatility of 1-nitro-3,3 `-dinitroazetidine (TNAZ): next generation powerful melt cast able high energy material - Talawar, M. B.; Singh, Alok; Naik, N. H.; Polke, B. G.; Gore, G. M.; Asthana, S. N.; Gandhe, B. R. (Journal of Hazardous Materials, 2006)
1-Nitro-3,3'-dinitroazetidine(TNAZ) was synthesized based on the lines of reported method. Thermolysis studies on synthesized and characterized TNAZ using differential scanning calorimetry (DSC) and hyphenated TG-FT-IR techniques were undertaken to generate data on decomposition pattern. FF-IR of decomposition products of TNAZ revealed the evolution of oxides of nitrogen and HCN containing species suggesting the cleavage of C/N-NO(2) bond accompanied with the collapse of ring structure. The effect of incorporation of 15% additives namely, 3-amino-1,2,4-triazole(AT), 3,5-diamino-1,2,4-triazole (DAT), carbohydrazide (CHZ), 5,7-dinitrobenzofuroxan (DNBF), bis (2,2-dinitropropyl) succinate (BNPS), triaminoguanidinium nitrate (TAGN), 2,4,6-trinitrobenzoic acid (TNBA) and nitroguanidine (NQ) on the volatility of TNAZ was investigated by undertaking thermogravimetric analysis. The TG pattern brings out the potential of BNPS and TAGN as additives to mitigate the volatility of TNAZ. The influence of additives on thermal decomposition of pattern of TNAZ was also investigated by DSC. The DSC results indicated that the additives did not have appreciable effect on the melting point of TNAZ. Scanning electron microscopic (SEM) studies were carried out to investigate the effect of additives on morphology of TNAZ. This paper also discusses the possible mechanism involved in between the TNAZ and TAGN and BNPS. It appears that the formation of charge transfer complex formation between the TNAZ and TAGN/BNPS. The effect of addition of high explosives such as CL-20, HMX and RDX on thermo-physical characteristics of TNAZ is also reported in this paper. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: melt castable explosive; morphological structure; synthesis; Thermolysis; trinitroazetidine (TNAZ); volatility behavior

Facile two-step chemoenzymatic access to natural germination inhibitor (+)-erigeronic acid A - Gogoi, Sanjib; N. P. Argade (Tetrahedron, 2006)
A facile two-step synthesis of natural germination inhibitor 5-butyl-3-oxo-2,3-dihydrofuran-2-yl-acetic acid [(+)-erigeronic acid A, 1] has been described via highly regioselective ring opening of (R)-acetoxysuccinic anhydride with the primary enolate of butyl methyl ketone, followed by an enzymatic hydrolysis and ail in situ dehydrative cyclization pathway with 77% overall yield. Oil the basis of the present chemoenzymatic approach, (R)-configuration has been assigned to the C-2 chiral centre of the natural erigeronic acid. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: (+)-erigeronic acid; (R)acetoxysuccinic anhydride; natural germination inhibitor; primary enolate of butyl methyl ketone; synthesis

Ligand-, copper-, and amine-free one-pot synthesis of 2-substituted indoles via Sonogashira coupling 5-endo-dig cyclization - Palimkar, Sanjay S.; Kumar, P. Harish; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron, 2006)
Results of the optimized conditions for the one-pot synthesis of 2-substituted indoles via palladium acetate catalyzed tandem Sonogashira coupling 5-endo-dig cyclization at room temperature under ultrasonic irradiation and standard stirred conditions are described. Electron-donating and electron-withdrawing groups present in both Coupling partners were well tolerated under these mild conditions. A copper-, ligand- and amine-free condition is an important feature of this protocol. Significant enhancement of reaction rates was observed for the reactions employing ultrasonic irradiation. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 5-endo-dig cyclization; Indole; synthesis; Ultrasound

Application of hydrolytic kinetic resolution (HKR) in the synthesis of bioactive compounds - Kumar, Pradeep; Naidu, Vasudeva; Gupta, Priti (Tetrahedron, 2007)
Keywords: Biological activity; bis-epoxides; Hydrolytic kinetic resolution; meso-epoxides; Natural products; synthesis; terminal epoxides

Controlled synthesis of low-molecular-weight polyethylene waxes by titanium-biphenolate-ethylaluminum sesquichloride based catalyst systems - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Applied Polymer Science, 2007)
Soluble complexes of titanium(IV) bearing sterically hindered biphenols, such as biphenol, 1,1'-methylene di-2-naphthol, 2,2'-methylene bis(4-chlorophenol), 2,2'-methylene bis(6-tert-butyl-4-ethyl phenol), and 2,2' ethylidene bis(4,6-di-tert-butyl phenol), were prepared and characterized. These catalyst precursors, formulated as [Ti((OO)-O-boolean AND)X-2], were active in the polymerization of ethylene at high temperatures in combination with ethylaluminum sesquichloride as a cocatalyst. The ultra-low-molecular-weight polyethylenes (PEs) were linear and crystalline and displayed narrow polydispersities. The catalytic polymerization leading to PE waxes in this reaction exhibited unique properties that have potential applications in surface coatings and adhesive formulations. (c) 2007 Wiley Periodicals, Inc.
Keywords: Catalysts; polyethylene (PE); synthesis; Ziegler-Natta polymerization

Hexamethyldisilazane-iodine induced intramolecular dehydrative cyclization of diamides: a general access to natural and unnatural quinazolinones - Kshirsagar, Umesh A.; Mhaske, Santosh B.; N. P. Argade (Tetrahedron Letters, 2007)
A simple and efficient general approach to various quinazolinone scaffolds, including peptidomimetic examples, has been demonstrated by employing HMDS/I-2 for the intramolecular dehydrative cyclization of diamides. The protecting groups -Boc, -Fmoc and -Cbz tolerated the present reaction conditions and we did not observe any racemization. The present protocol has also been used as a key step for the efficient four-step syntheses of the naturally occurring quinazolinones, sclerotigenin, (-)-circumdatin-F and (-)-fumiquinazoline-F. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: diamides; HMDS/I-2; intramolecular dehydrative cyclizations; natural and unnatural quinazolinones; synthesis

NCL-7, a novel all silica analog of polymorph B rich member of BEA family: synthesis and characterization - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
{Polymorph B-rich BEA type structure, NCL-7, was synthesized using hydrothermal method in fluoride medium using perchloric acid as promoter. The samples were characterized using XRD, low temperature N-2-adsorption and Si-29 MASNMR. As the structure of beta is highly disordered Rietveld refinement of powder XRD patterns is precluded. Phase composition is derived using the simulated patterns for the random intergrowths of polymorph A and B by DIFFaX. The stacking direction c' is perpendicular to the a'b' plane of the layer. The composition of polymorph B is found to be ca. 60-65%. Two other structures namely NCL-5 and NCL-6 with varying degree of polymorph B enrichment were also synthesized. Synthesis parameters such as effect of H2O/SiO2, TEAOH/SiO2, HClO4/SiO2 and crystallization temperature were studied thoroughly. The present article explains for the first time the synthesis and characterization of NCL-7, an analog of BEA type family with enrichment of polymorph B and its comparison with normal beta (*
Keywords: B-polymorph; DIFFaX; Promoter; Reitveld refinement; synthesis; zeolite beta

Synthesis and characterization of NCL-5, NCL-6 and NCL-7: new zeolites enriched with polymorph B of the BEA family - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Gupta, Narendra M.; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
The synthesis of all-silica analogs of polymorph B-enriched zeolites of the BEA family denoted as NCL-5, NCL-6 and NCL-7 was realized hydrothermally at lower water content in fluoride medium using perchloric acid as promoter and terraethylammonium hydroxide as template. The present article explains the effect of different synthesis parameters on NCL-5, NCL-6 and NCL-7. The samples were characterized using XRD, low temperature N-2-adsorption, Si-29 MAS NMR and FTIR spectroscopy. The phase composition of the structures was derived using simulated patterns for the random intergrowths of polymorphs A and B using DIFFaX Code. The stacking direction c' is perpendicular to the a'b' plane of the layer. The phase composition of polymorph B derived using DIFFaX code was found to be 90-95%. 70-75% and 60-65% in NCL-5, NCL-6 and NCL-7, respectively. The gradual decrease of polymorph B concentration in these samples showed a correlation with the decrease in water/SiO2 molar ratio in gel. The framework FTIR spectral analysis of NCL-5 and all-silica-beta supported the postulation that significant enrichment of polymorph B in NCL-5 compared to that in all-silica-beta, as indicated by the relative intensities of pair of bands at 1097 and 1018 cm(-1) and 460 and 423 cm(-1) vibrations, leads to more tortuous channel structure associated with polymorph B. (C) 2007 Elsevier Inc. All riahts reserved.
Keywords: BEA family; NCL-5; NCL-6; NCL-7; polymorph B enrichment; synthesis; zeolites

Synthesis and MASNMR characterization of VPI-5 molecular sieve - Venkatathri, N. (Asian Journal of Chemsitry, 2007)
The synthesized VPI-5 sample was characterized by XRD, SEM, FTIR, TG/DTA, Al-27, P-31 and 3Q MASNMR techniques, which shows that the sample was highly crystalline. Carbon and nitrogen analysis reveals that the sample contains no template molecules; however, TG/DTA analysis shows the presence of physisorbed template molecules. MASNMR results show the presence of two different types of aluminium and phosphorus, 3Q MASNMR shows the presence of two types of environmentally different tetrahedral aluminium, which are not observable by ordinary MASNMR along with known octahedral aluminium.
Keywords: 3Q-MASNMR; FTIR; MASNMR; SEM; synthesis; TG/DTA; VPI-5; XRD

Synthesis of poly(aniline-co-o-toluidine) coatings and their corrosion-protection performance on low-carbon steel - Pawar, Pritee; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2007)
Strongly adherent poly(aniline-co-o-toluidine) coatings were synthesized on low-carbon-steel substrates by the electrochemical copolymerization of aniline with o-toluidine with sodium tartrate as the supporting electrolyte. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and scanning electron microscopy. The formation of the copolymer with the mixture of monomers in the aqueous sodium tartrate solution was ascertained by a critical comparison of the results obtained from the polymerizations of the individual monomers, aniline and o-toluidine. The optical absorption spectrum of the copolymer was drastically different from the spectra of the respective homopolymers, polyaniline and poly(o-toluidine). The extent of the corrosion protection offered by poly(aniline-co-o-toluidine) coatings to low-carbon steel was investigated in aqueous 3% NaCl solutions by open-circuit-potential measurements and a potentiodynamic polarization technique. The results of the potentiodynamic polarization measurements showed that the poly(aniline-co-o-toluidine) coatings provided more effective corrosion protection to low-carbon steel than the respective homo-polymers. The corrosion rate depended on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (c) 2006 Wiley Periodicals, Inc.
Keywords: Coatings; conducting polymers; copolymerization; synthesis

Use of poly(o-toluidine)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel - Chaudhari, Sudeshna; Patil, P. P.; Mandale, A. B.; Patil, K. R.; Sainkar, S. R. (Journal of Applied Polymer Science, 2007)
This study explored the possibility of using poly(o-toluidine) (POT)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel in a chloride environment. POT/ZrO2 nanocomposite coatings were synthesized on steel substrates through an electrochemical route. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The performance of POT/ZrO2 nanocomposites as protective coatings against the corrosion of mild steel in aqueous 3 wt % NaCl was evaluated with the potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of this study demonstrate that POT/ZrO2 nanocomposite coatings provide better protection for mild steel against corrosion than pure POT coatings. The corrosion potential was about 0.312 V versus a saturated calomel electrode, more positive in aqueous 3 wt % NaCl for the nanocomposite-coated steel than the uncoated steel, and the corrosion rate of steel was reduced by a factor of almost 51. (c) 2007 Wiley Periodicals, Inc.
Keywords: Coatings; conjugated polymers; FTIR; Nanocomposites; synthesis

Hydrated clay for catalyst removal in copper mediated atom transfer radical polymerization(a) - Munirasu, Selvaraj; Deshpande, Ashwini; Baskaran, Durairaj (Macromolecular Rapid Communications, 2008)
A simple method has been described to remove catalyst from the copper mediated atom transfer radical polymerization (ATRP) of benzyl methacrylate and methyl methacrylate in anisole at 25 degrees C using hydrated natural clay (sodium montmorillonite, Na-clay). The method consists of (1) addition of hydrated clay (CU(I/)clay approximate to 5 wt.-%) either during or after the polymerization, (2) oxidation of catalyst complex by exposing the terminated reaction mixture in air, and (3) filtration to obtain catalyst free polymer solution. A strong coordination of CuBr-ligand complex onto hydrated clay (10 wt.-%
Keywords: Atom transfer radical polymerization (ATRP); Catalysts; clay; selectivity; synthesis

Hydrazine based facile synthesis and ordered assembly of metal nanoparticles (Au, Ag) on a bacterial surface layer protein template - Puranik, Sarang S.; Joshi, Hrushikesh M.; Ogale, S. B.; Paknikar, K. M. (Journal of Nanoscience and Nanotechnology, 2008)
An efficient and facile procedure is developed for concurrent in situ synthesis and ordered assembly of metal nanoparticles on a periodic two dimensional protein array. The S-layer protein of Bacillus subtilis exhibiting uniform pore size is used as template. Synthesis of gold and silver nanoparticles anchoring on the pores of S-layer is achieved by chemical reduction of respective metal salt laden protein template. Transmission electron microscopy reveals formation of well ordered and separated gold and silver nanoparticles with an average diameter of 6 +/- 1 nm and 4 +/- 1 nm, respectively. The periodic arrangement of nanoparticles is dictated by the native structure of S-layer protein array as the nanoparticle locations are found to be correlated to the nanosized pores of the crystalline S-layer array.
Keywords: Bacteria; Metal Nanoparticles; synthesis

Synthesis and characterization of novel polybenzimidazoles bearing pendant phenoxyamine groups - Kulkarni, Mahesh; Potrekar, Ravindra; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
A novel aromatic diacid, 3, 5-dicarboxyl-4'-amino diphenyl ether, containing pendant phenoxy amine group was synthesized. Homo- and co-polybenzimidazoles containing different content of pendant phenoxyamine groups were synthesized by condensation of 3,3'-diaminobenzidine with this acid and a mixture of this acid and isophthalic acid in different ratio in polyphosphoric acid. Copolybenzimidazoles with structural variations were also synthesized based on this acid and pyridine dicarboxylic acid, terephthalic acid, adipic acid, or sebacic acid. The polymers have good solubility in polar aprotic solvents and strong acids and they form tough flexible films by solution casting. The polymers were characterized by different instrumental techniques (FTIR, TGA, DSC, XRD, etc.) and for solvent solubility, mechanical properties, inherent viscosity, and proton conductivity. The inherent viscosities of the polymers vary in the range of 0.62-1.52 dL/g. They have high thermal stability up to 475506 degrees C (IDT) in nitrogen, high glass transition temperatures (T-g) ranging from 313 to 435 degrees C and good tensile strength ranging from 58 to 125 MPa. Proton conductivity of homo polymer is 3.72 x 10(-3) S/cm at 25 degrees C and 2.45 x 10(-2) S/cm at 200 degrees C (c) 2008 Wiley Periodicals, Inc.
Keywords: Characterization; copolybenzimidazoles; High performance polymers; high temperature materials; pendant phenoxyamine group; polybenzimidazoles; synthesis

Synthesis of amphiphilic poly(methyl methacrylate-b-ethylene oxide) copolymers from monohydroxy telechelic poly(methyl methacrylate) as macroinitiator - Dhara, Mahua Ganguly; Baskaran, Durairaj; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
The synthesis of well-defined poly(methyl methacrylate)-block-poly(ethylene oxide) (PMMA-b-PEO) dibock copolymer through anionic polymerization using monohydroxy telechelic PMMA as macroinitiator is described. Living anionic polymerization of methyl methacrylate was performed using initiators derived from the adduct of diphenylethylene and a suitable alkyllithium, either of which contains a hydroxyl group protected with tert-butyldimethylsilyl moiety in tetrahydrofuran (THF) at -78 degrees C in the presence of LiClO4. The synthesized telechelic PMMAs had good control of molecular weight with narrow molecular weight distribution (MWD). The H-1 NMR and MALDI-TOF MS analysis confirmed quantitative functionalization of chain-ends. Block copolymerization of ethylene oxide was carried out using the terminal hydroxyl group of PMMA as initiator in the presence of potassium counter ion in THF at 35 degrees C. The PMMA-b-PEO diblock copolymers had moderate control of molecular weight with narrow MWD. The H-1 NMR results confirm the absence of trans-esterification reaction of propagating PEO anions onto the ester pendants of PMMA. The micellation behavior of PMMA-b-PEO diblock copolymer was examined in water using H-1 NMR and dynamic light scattering. (C) 2008 Wiley Periodicals, Inc.
Keywords: Anionic polymerization; block copolymers; synthesis

Carboxylic-functionalized water soluble pi-conjugated polymer: highly selective and efficient chemosensor for mercury(II) ions - Balamurugan, A.; Reddy, M. L. P.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Here, we report a new carboxylic-functionalized water soluble pi-conjugated polymer for selective detection of highly toxic Hg(2+) in neutral pH condition. carboxylic-functionalized thiophene containing oligophenylenevinylene was synthesized and polymerized under oxidative route to obtain water soluble polymer. Free carboxylic groups present in the pi-conjugated materials provide opportunity to use pH as external stimuli for studying secondary interaction such as hydrogen bonding and aromatic pi-stacking of the chromophores. The pH changes strongly influence on the molecular interactions in the monomer, whereas the long chain polymer was less disturbed. The polymer showed high selectivity for detecting Hg(2+) ions compared with any other transition metal ions in water. The detection efficiency of the polymer was found almost 40 times higher than that of its monomeric unit. Stern-Volmer constant for the Hg(2+) ion sensing was determined through concentration dependent studies as 6.4 x 10(5) M(-1). The carboxylic-functionalized polymer showed reversibility in the metal-ion detecting capabilities which was further investigated by NaCl complexation with Hg(2+) complex. Both funneling of excitation energy to the Hg(2+) center and also excitation energy migration through chain pi-conjugated backbone were correlated to the superior sensing characteristics of the polymer compared to its monomeric counterpart. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 5144-5157, 2009
Keywords: conjugated polymer; pH sensitive; photophysical studies; sensing; synthesis; water soluble

Dependence of Si-29 NMR chemical shielding properties of precursor silicate species, Q(0) on its local structure at the pre-nucleation stages of zeolite synthesis - a DFT based computational correlation - Selvaraj, Kaliaperumal; Kurian, Reshmi (Microporous and Mesoporous Materials, 2009)
The exploration for new zeolite structures with tailored framework architectures for enhanced catalytic applications requires the knowledge about their nucleation and crystallization at molecular level. Nuclear magnetic resonance (NMR) is one of the most widely tried techniques to understand this. However, by NMR, it is difficult to accurately assign the molecular level precursor silicate structures at the pre-nucleation stages of zeolite synthesis. Hence, understanding the chemical shielding of such precursor molecules using quantum mechanical (QM) computations is extremely useful. Alkali is a fundamental component in the alkali based hydrothermal zeolite synthesis and its nature plays a major role. In the present report, we attempt to understand the differences in the local structure of the primary building block such as Si(OH)(4) (Q(0) silicate species) due to the associated alkali and their influence on NMR chemical shielding properties. Present work reports the calculation of Si-29 NMIR isotropic chemical shifts of T species with different cations such as Na, K and Ca using density functional theory (DFT). Results of natural bonding orbital (NBO) analysis, Perturbation theory energy analysis and electron density iso-surfaces were employed to obtain a deeper insight about their influence on the chemical shielding and on zeolite synthesis. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Ab initio method; Density Functional Theory (DFT); Electron density; NBO analysis; Perturbation theory; Q(0) silicate species; Si-29 NMR chemical shift; synthesis; zeolite

Effect of sintering temperature and thermoelectric power studies of the system MgFe2-xCrxO4 - Hankare, P. P.; Vader, V. T.; Sankpal, U. B.; Gavali, L. V.; Sasikala, R.; Mulla, Imtiaz S. (Solid State Sciences, 2009)
Mixed metal oxides showing the spinel structure exhibit interesting structural and electrical properties. Substances with specific compositions in the system MgFe2-xCrxO4 were synthesized by the simple co-precipitation method and have been investigated by X-ray diffraction (XRD) and scanning electron microscope (SEM) to study the effect of temperature on the size of particles and grains. The infrared spectrum shows, two strong bands around 600 and 500 cm(-1). An elemental composition of one of the samples, MgFeCrO4 was found by energy dispersive X-ray spectroscopy (EDS). The thermoelectric power measurements carried out from room temperature to 500 degrees C, show both n-type and p-type behavior. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: synthesis; Temperature effect; Thermoelectric studies

Hydrolytic kinetic resolution as an emerging tool in the synthesis of bioactive molecules - Kumar, Pradeep; Gupta, Priti (Synlett, 2009)
A variety of racemic epoxides mainly derived from terminal olefins, such as aliphatic epoxides, multifuncitonalized epoxides and amine-substituted epoxides, have been successfully resolved into the enantiomerically pure epoxides and diols using Jacobsen's hydrolytic kinetic resolution (HKR) method. The chiral epoxides thus prepared were further elaborated by synthetic manipulation to provide a variety Of Compounds of biological interest. A general synthetic strategy for the construction Of S synlanti-1,3-polyol systems using iterative HKR has been developed, which was subsequently utilized in the synthesis of natural products with a broad range of biological activity. The protocol for the 1,3-polyols was also further extended to the synthesis of 1,3-amino alcohols.
Keywords: Biological activity; Hydrolytic kinetic resolution; Natural products; synthesis; terminal epoxides

Solid state synthesis and room temperature magnetic properties of iron phosphide nanoparticles - Singh, N.; Khanna, P. K.; Joy, Pattayil Alias (Journal of Nanoparticle Research, 2009)
Room temperature magnetic properties have been achieved for nano-crystalline iron phosphide synthesized from the direct solid state reaction of iron chloride and tri-octylphosphine (TOP). The magnetization continuously increased with higher magnetic fields, indicating a super-paramagnetic behavior. It is observed that room temperature magnetism is possible for the material showing antiferromagnetic nature at low temperatures. In the present synthesis, TOP acted as a source of phosphorus as well as a surfactant. X-ray diffraction (XRD) studies revealed that the black powder is a mixture of FeP and Fe(2)P. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) showed elongated as well spherical particles. Energy dispersion X-ray analysis (EDAX) confirmed a non-stoichiometric iron phosphide. Presence of TOP was confirmed by infra-red (IR) spectroscopy, and thermo-gravimetric analysis (TGA) indicated about 6% wt. loss due to presence of organics.
Keywords: Iron phosphide; Semiconductors; Solid state reaction; synthesis; XRD

Synthesis and characterization of novel schiff base polyurethanes - Raghu, A. V.; Gadaginamath, G. S.; Jeong, Han Mo; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2009)
Eight different types of novel polyurethanes (PUs) were synthesized through the polyaddition reaction of 4,4'-(ethane-1,2-diylidenedinitrilo)diphenol and 4,4'(pentane-1,5-diylidenedinitrilo)diphenol with four different diisocyanates: 4,4'-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate. The resulting PUs were soluble in polar, aprotic solvents. Structures of the diols and PUs were established with Ultraviolet-visible, fluorescence, Fourier transform infrared (FTIR), (1)H-NMR, and (13)C-NMR spectroscopy data. FTIR and NMR spectral data indicated the disappearance of both hydroxyl and isocyanate groups in the PUs. The thermal properties were investigated with thermogravimetry and differential scanning calorimetry. The weight losses, glass transitions, onset temperatures, and crystalline melting temperatures were measured. All the PUs exhibited semicrystalline and amorphous morphologies, as indicated by X-ray diffraction. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 113: 2747-2754, 2009
Keywords: amorphous; Morphology; polyurethanes; synthesis; Thermal properties

Facile synthesis of N-substituted maleimides - Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Chaudhary, Preeti M. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
A simple and efficient method for the synthesis of N-substituted malemides from the corresponding maleamie acids under the phase transfer catalysis has been described
Keywords: Maleamic acids; maleimides; phase transfer catalysis; synthesis

General approach to 2,4-dialkyl-3-carboxybutyrolactones: an efficient synthesis of (+/-)-striatisporolide A and (+/-)-lichesterinic acid - Patel, Ramesh M.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2010)
Starting from 2-alkylidene-3-methylsuccinimides, simple and efficient synthesis of the natural products striatisporolide A. lichesterinic acid and lichesterylic acid have been demonstrated via an acid catalyzed hydrolysis, esterification, OsO(4)-dihydroxylation and dehydrative cyclization pathway.
Keywords: 2-Alkylidene-3-methylsuccinimides; dehydrative cyclizations; lichesterinic acid; OsO(4)-dihydroxylation; striatisporolide A; synthesis

Nitrophenoxy groups containing polybenzimidazoles as polymer electrolytes for fuel cells: synthesis and characterization - Kulkarni, Mahesh; Potrekar, Ravindra; Kulkarni, R. A.; Vernekar, S. P. (Journal of Applied Polymer Science, 2010)
Polybenzimidazoles containing different contents of pendant nitrophenoxy groups were prepared by condensation of 3,3'-diamino-benzidine with a mixture of 3,5-dicarboxyl-4'-nitro diphenyl ether and isophthalic acid (IPA) in different ratios in polyphosphoric acid. The polymers are soluble in polar aprotic solvents, they have inherent viscosities in the range of 0.75-1.10 dL g(-1) and they form tough and transparent films on solution casting. They have good thermal stability with initial decomposition temperature ranging from 380 to 416 degrees C in nitrogen, good tensile strength ranging from 56 to 65 MPa and reasonably good oxidative stability. Phosphoric acid uptake of these polymers is low compared with PBI and membranes doped with phosphoric acid exhibit good proton conductivity in the range of 6.6x 10(-3) to 1.9x 10(-2) S/cm at 25 degrees C and 1.2x 10(-2) to 4.9x 10(-2) S/cm at 175 degrees C, compared with 3.9x 10(-3) S/cm at 25 degrees C and 3.2x 10(-2) S/cm at 175 degrees C for PBI. These membranes are suitable for applications as polymer electrolyte for fuel cell and presumably for gas separation at high temperature. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 3282-3292, 2010
Keywords: Characterization; membranes; pendant nitrophenoxy group; polybenzimidazoles; proton conductivity; synthesis

Synthesis of (R)-coniine and (S)-coinicine via organocatalytic alpha-aminoxylation of an aldehyde - Kondekar, Nagendra B.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A short and efficient synthesis of the indolizidine alkaloid (S)-coinicine has been achieved using organocatalytic sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of an aldehyde catalyzed by L-proline. Similarly, a common organocatalytic alpha-aminoxylation route has been developed for the asymmetric synthesis of both (R)-coniine and (S)-coinicine.
Keywords: hemlock alkaloids; organocatalysis; Proline; sequential reactions; synthesis

Design, synthesis and biological evaluation of peptidyl-vinylaminophosphonates as novel cysteine protease inhibitors - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Bioorganic & Medicinal Chemistry, 2011)
We report herein, design and synthesis of vinylaminophosphonates, a novel class of compounds as possible cysteine protease inhibitors. The synthesis of vinylaminophosphonates has been accomplished employing Tsuji-Trost reaction as a key step. The synthesized compounds were assayed against papain, a model cysteine protease and some of our synthesized compounds showed IC50 values in the range of 30-54 mu M thereby suggesting that these chemical entities thus could constitute an interesting template for the design of potential novel protease inhibitors. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cysteine; Inhibitor design; Protease inhibitors; synthesis; Tsuji-Trost reaction; Vinylaminophosphonates

First total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one: a cancer chemopreventive agent - Borikar, Sanjay P.; Paul, Vincent; Puranik, Vedavati G.; Sathe, Vilas T.; Lagunas-Rivera, Selene; Ordonez, Mario (Synthesis-Stuttgart, 2011)
The first total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one, a newly discovered natural product with anticancer property is described by two different routes. A sequence involving an incorporation of a methyl group via a Gilman reagent and a chemoselective reduction of a cyclic anhydride functionality are the key steps. The methods proposed start from easily available starting materials and allow ready preparation of the final compound in good overall yield.
Keywords: Allium cepa; chemopreventive; Gilman reagent; selective; synthesis

Glycerol mediated low temperature synthesis of nickel nanoparticles by solution reduction method - Singh, Kalpana; Kate, Kunal H.; Chilukuri, V. V. Satayanarayana; Khanna, P. K. (Journal of Nanoscience and Nanotechnology, 2011)
Phase pure Nickel nano-particles were synthesized by in-situ generation of nickel hydrazine hydrate complex (Ni-HH) followed by its decomposition in an alkaline glycerol medium. The synthesis can be performed in an open beaker with or without the use of surface protective reagents. By using the present method, Ni nano-particles can be prepared in large scale. The black nano-powders so-obtained were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED), Scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infra-red (FTIR) spectroscopy and thermal analysis (TGA). XRD and SAED analysis revealed that the synthesized particles were pure crystalline nickel with FCC structure.
Keywords: Chemical Reduction; Nano-Particles; synthesis; Transition Metal; XRD

Regioselective NaBH4 and DIBAL-H reductions of 3,4-dimethoxyhomopiperonylphthalimide: concise and efficient synthesis of nuevamine and isonuevamine - Wakchaure, Prasad B.; Kunte, Sunita S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2011)
Facile synthesis of nuevamine and isonuevamine has been reported via the regioselectivc reduction of hindered and unhindered carbonyl groups of 3,4-dimethoxyhomopiperonylphthalimide, respectively using sodium borohydridc and diisobutylaluminum hydride, Mowed by an acid catalyzed intramolecular dehydrative cyclization pathways. The chemistry involved in obtaining the regioselectivity has been discussed in brief.
Keywords: 6-dimethoxyhomophthalimide; intramolecular dehydrative cyclizations; isonuevamine; N-Homopiperonyl-5; nuevamine; regioselective reductions; synthesis

Efficient synthesis of a hydroxyethylamine (HEA) isostere and its alpha-aminophosphonate and phosphoramidate derivatives as potential anti-HIV agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Pannecouque, Christophe; De Clercq, Eric (Chemmedchem, 2012)
HIV protease is a promising drug target for AIDS therapy, and several potent HIV-1 protease inhibitors have been reported to date. Although existing inhibitors exhibit high selectivity, they have also been associated with severe side effects and the possible emergence of therapeutic resistance. As HIV protease cleaves the peptide bond via a tetrahedral intermediate, various transition-state models such as hydroxyethylamine (HEA) have been designed. We therefore pursued an efficient synthesis of an HEA isostere; this was performed with a novel one-pot reductiontransiminationreduction reaction sequence as a key step. a-Aminophosphonate and phosphoramidate derivatives of the HEA isostere were designed and synthesized, and all of the synthesized derivatives were assayed for their anti-HIV activities against wild-type and mutant HIV strains. Phosphoramidate derivative 15?a was found to be the most active of all synthesized compounds against the IIIB and RES056 strains. As phosphonates are known to exhibit physiological stability, good cell permeability, and other promising pharmacokinetic characteristics, our newly synthesized compounds have the potential as alternatives to existing therapeutics and diagnostics.
Keywords: a-aminophosphonates; antiviral agents; hydroxyethylamine isosteres; phosphoramidates; synthesis

Sono-chemical synthesis of ZnO nano-particles and their application in hydrogen sulphide gas sensing - Khanna, P. K.; Kate, Kunal; Dhanabalan, K.; Banerjee, Shaibal; Reji, Nedunnkandathil; Shinde, S. D.; Jain, G. H. (Journal of Nanoscience and Nanotechnology, 2012)
Herein we describe synthesis of ZnO nanoparticles by using alkaline solution of ZnX2 (X = NO3, Cl) under ultrasound energy of 20 KHz. The reaction can be completed in about 1-2 hours. As prepared powders were analyzed by XRD measurement to find that the product is hexagonal phase pure ZnO. UV-Visible measurement of aq. solution showed absorption band at similar to 365 nm and photoluminescence (PL) indicated multiple bands in visible region due to deep traps owing to high temperature sintering. The hydrophilicity can be imparted by use of a suitable polyelectrolyte. Freshly prepared samples showed good dispersion in aqueous and alcoholic medium. The thick films derived from the ZnO nano-particles showed excellent sensing for hydrogen sulphide gas.
Keywords: Gas-Sensing; Sono-Chemical; synthesis; ZnO Nano-Particles

Biology-orientated synthesis of putrescine bisamides gigantamide A, dasyclamide, and cucullamide - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2013)
Starting from putrescine and the requisite carboxylic acids, first syntheses of bioactive natural products gigantamide A, dasyclamide, and cucullamide were accomplished in very good overall yields using an appropriate sequence of dehydrative coupling reactions. The syntheses of the corresponding dehomo analogues of these natural products are also described. Regioselective diisobutylaluminum hydride reduction of an unhindered carbonyl group in citraconimide is the key step.
Keywords: dehydrative coupling reactions; diamines; natural and unnatural bisamides; regioselective reduction; synthesis

Novel vanadium n-propylamino phosphate catalyst: synthesis, characterization and applications - Anumula, Rajini; Nookaraju, Muralasetti; Selvaraj, Kaliaperumal; Reddy, Ingala Ajit Kumar; Narayanan, Venkatathri (Materials Research-Ibero-American Journal of Materials, 2013)
A novel, lamellar type Vanadium n-propylamino phosphate catalyst is synthesized and characterized by using various physicochemical techniques such as Powder X-ray diffraction, Scanning electron microscopy/Energy dispersive X-ray analysis, Thermogravimetry/Differential thermal analysis, Fourier transform Infrared analysis, Electron spin resonance spectroscopy, Ultraviolet - Visible Diffuse reflectance spectroscopy, X-ray Photoelectron spectroscopy, P-31 Magic angle spinning Nuclear Magnetic Resonance spectroscopy and Catalytic applications toward Octahydroquinazolinone synthesis. It is found that the n-propylamine is present as sandwich between Vanadyl phosphate layers. Most of the Vanadium is present as V4+ ions in tetrahedral co-ordination. Vanadium n-propylamino phosphate catalyses Octahydroquinazolinone synthesis more effeciently and the optimum conditions required for Octahydroquinazolinone synthesis are, Benzaldehyde (2 mmol), Dimedone (2 mmol), Urea (4 mmol), Methanol + Water (1:1, 5 mL) and Catalyst (0.05 g). A plausible mechanism is also proposed.
Keywords: n-propylamino phosphate; octahydroquinazolinones; synthesis; Vanadium

Phytosynthesis of silver nanoparticles by semecarpus anacardium L. leaf extract - Raju, D.; Hazra, Sulekha; Mehta, Urmil J. (Materials Letters, 2013)
Green synthesis of silver nanoparticles (AgNPs) using Semecmpus anacardium L leaf extract was studied. The reduction of silver (Ag+) ions was characterized by using UV-vis spectrophotometer showing formation of AgNPs within 15-20 mm. A time dependent reaction showed the increase in the nanoparticles (NPs) with time. Transmission electron microscopy (TEM) analysis showed that the synthesized AgNPs varied from 10 to 25 nm and has spherical shape. The Fourier transform infrared (FTIR) analysis showed that phenols and protein were responsible for the formation of the AgNPs. The energy dispersive spectroscopy (EDAX) analysis confirms the formed NPs were of silver. The quantification of AgNPs was studied by inductive coupled plasma spectrometry (ICP-AES). The important outcome of this work can be value addition to the medicinal plants in synthesis of NPs for biomedical applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: FTIR; Leaf extract; Nanoparticles; Semecarpus anacardium; synthesis; TEM

Biological synthesis of cationic gold nanoparticles and binding of plasmid DNA - Raju, D.; Vishwakarma, Rishi K.; Khan, Bashir Mohammad; Mehta, Urmil J.; Ahmad, Absar (Materials Letters, 2014)
Nanobiotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials. The present work focuses on synthesis of cationic gold nanoparticles (C-GNPs) for biological applications, especially in gene and drug delivery studies. A biosynthesis methodology has been developed for the functionalization of gold nanoparticles to cationic nature. The synthesis of C-GNPs was done by using peanut leaf extract in the presence of cysteamine. The formed C-GNPs were characterized by using UV-visible spectroscopy (UV-vis), the particles sizes and shapes were confirmed by a Transmission electron microscope (TEM) and crystallinity of C-GNPs was characterized by diffraction. The binding of plasmid DNA on the C-GNPs was confirmed by agarose gel electrophoresis. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Cationic; Nanoparticles; Plasmid DNA; synthesis; TEM

CdS nanowires: ultra-long growth and enhanced field emission properties - Chavan, Padmakar G.; Kashid, Ranjit V.; Badhade, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Vaccum, 2014)
Here, we report the synthesis of ultra-long CdS nanowires with aspect ratio similar to 8 x 10(4) by simple route of thermal evaporation technique. A change in the vertical arrangement of quartz boats leads in to the synthesis of ultra-long CdS nanovvires via high degree of condensation. This technique is seen to be cost effective and easy. The growth of the nanowires is found to be increased very rapidly from few micrometers to few millimeters. The possible reason for the growth of the ultra-long CdS nanowires is discussed in detail. The turn-on field defined for the current density of similar to 0.1 mu A/cm(2) has been found to be similar to 1.4, 1.45, 1 and 0.17 V/mu m for specimen A, B, C and D (specimens A-D, synthesized by variation in synthesis parameters) respectively. The turn-on field of the specimen D (similar to 0.17 V/mu m) is found to be quite superior than the value reported for other CdS nanoforms which is very remarkable. Simple way of bulk fabrication leads to the low turn-on value which indicates a possible use of the present emitter in the micro/nanoelectronics devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current stability; field emission; synthesis

Extracellular synthesis of silver nanoparticles using living peanut seedling - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Applied Nanoscience, 2014)
Synthesis of nanoparticles by environment friendly method is an important aspect of nanotechnology. In the present study, extracellular reduction of silver ions to silver nanoparticles was carried out using living peanut plant. The electron microscopic analysis shows that the formed nanoparticles were of different shapes and sizes. The formed nanoparticles were polydispersed. The shapes of the nanoparticles were spherical, square, triangle, hexagonal and rod. Most of the particles were spherical and 56 nm in size. EDS analysis confirmed the formed nanoparticles were of silver. The crystalline nature of nanoparticles was confirmed by diffraction. This method opens up an exciting possibility of plant-based synthesis of other inorganic nanomaterials. This study confirms the synthesis of extracellular silver nanoparticles by living plant.
Keywords: Nanoparticles; Shapes; Silver; synthesis; TEM

Living plant-mediated synthesis of different shaped gold nanoparticles - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Nanoscience and Nanotechnology Letters, 2014)
We demonstrate extracellular green synthesis of gold nanoparticles with different shapes and sizes by using live Prosopis juliflora L. seedling. The conversion of ionic to metallic gold nanoparticles by P. juliflora seedling was carried out in short period. The formed nanoparticles were characterized by UV, TEM, Diffraction and EDS. TEM shows well dispersed particles of different shapes and sizes. The percentage of different shapes of nanoparticles was calculated, most of the particles were spherical in shape (75%). The triangle nanoparticles were 10%, followed by squares (8%), hexagonal (5%) and rods (2%). The diffraction shows the formed nanoparticles are crystalline in nature and EDS confirms the formed nanoparticles are of gold. This shows P. juliflora seedling can synthesis different shapes of well dispersed nanoparticles.
Keywords: Gold; Nanoparticles; Prosopis juliflora; Shapes; synthesis; TEM

Metal-catalyzed cross-coupling reactions of halomaleic anhydrides and halomaleimides: synthesis of structurally interesting and biologically important natural and unnatural products - Deore, Prashant S.; N. P. Argade (Synthesis-Stuttgart, 2014)
This brief review presents a concise literature account of the metal-catalyzed cross-coupling reactions of halomaleic anhydrides and halomaleimides leading to significant synthetic and natural products. Metal-catalyzed Heck, Suzuki-Miyaura, Stille-Migita, Negishi, Hiyama, and Sonogashira cross-coupling reactions with palladium as the key element are discussed. The metal-catalyzed exchange of a vinylic leaving group by a carbon nucleophile, the SNV reaction, gives a diverse range of bioactive natural and unnatural products.
Keywords: bioactive natural and unnatural products; halomaleic anhydride; halomaleimide; metal-catalyzed cross-coupling; synthesis

Protein mediated synthesis of Au-Ag bimetallic nanoparticles - Raju, D.; Mendapara, Ritul; Mehta, Urmil J. (Materials Letters, 2014)
There is growing need to develop environment friendly method for synthesis of bimetallic nanoparticle that do not use toxic chemicals during their synthesis process. Here, we report synthesis of Au-Ag bimetallic nanoparticles by using macerase enzyme as reducing agent at different temperatures. Bimetallic nanoparticles were synthesized at 80 and 90 degrees C. The intensity of formation of nanoparticles was more at 80 degrees C. The bimetallic nanoparticles are characterized by using UV-vis, TEM and EDAX. The TEM study shows the inner gold and outer silver bimetallic nanoparticles. The formed nanoparticles are 4-20 nm in size and spherical in shape. EDAX confirms the formed bimetallic nanoparticles are of gold and silver. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Enzyme; Gold; Macerase; Particles; Silver; synthesis

Synthesis of chenopanone - Deore, Prashant S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Starting from glyoxalic acid, a facile three step approach to chenopanone has been described utilizing the Barbier reaction as a key step.
Keywords: acid hydrolysis; Barbier reaction; chenopanone; condensation; Glyoxalic acid; isovaleraldehyde; synthesis

Role of chemical reactivity and transition state modeling for virtual screening - Karthikeyan, Muthukumarasamy; Vyas, Renu; Tambe, Sanjeev S.; Radhamohan, Deepthi; Kulkarni, Bhaskar D. (Combinatorial Chemistry & High Throughput Screening, 2015)
Every drug discovery research program involves synthesis of a novel and potential drug molecule utilizing atom efficient, economical and environment friendly synthetic strategies. The current work focuses on the role of the reactivity based fingerprints of compounds as filters for virtual screening using a tool ChemScore. A reactant-like (RLS) and a product-like (PLS) score can be predicted for a given compound using the binary fingerprints derived from the numerous known organic reactions which capture the molecule-molecule interactions in the form of addition, substitution, rearrangement, elimination and isomerization reactions. The reaction fingerprints were applied to large databases in biology and chemistry, namely ChEMBL, KEGG, HMDB, DSSTox, and the Drug Bank database. A large network of 1113 synthetic reactions was constructed to visualize and ascertain the reactant product mappings in the chemical reaction space. The cumulative reaction fingerprints were computed for 4000 molecules belonging to 29 therapeutic classes of compounds, and these were found capable of discriminating between the cognition disorder related and anti-allergy compounds with reasonable accuracy of 75% and AUC 0.8. In this study, the transition state based fingerprints were also developed and used effectively for virtual screening in drug related databases. The methodology presented here provides an efficient handle for the rapid scoring of molecular libraries for virtual screening.
Keywords: fingerprints; intermediates; metabolic pathways; product-like score; reactant-like score; reaction; screening; synthesis; virtual screening

Dexterous route for synthesis of hollow spherical ZnO and ZnO-Ag nanocomposite with superior photocatalytic ability - Maity, Jayeta; Bhattacharjee, Gourab; Satpati, Biswarup; Sardar, Debasmita; Ghosalya, Manoj Kumar; Bala, Tanushree (ChemistrySelect, 2019)
Hollow spherical ZnO and hollow ZnO-Ag nanocomposites with variable percentage of loading of Ag content were successfully fabricated through a novel, template free and easily reproducible route. Extensive characterizations were carried out using FTIR, XRD, XPS, BET, TEM and SEM. The hollow morphology of the particle and the composite encouraged a detailed photocatalysis study in comparison to solid commercial ZnO and the corresponding ZnO-Ag composite. The photocatalytic activity of the hollow particle and the composite was assessed monitoring the decolouration of methylene blue dye using UV-Vis absorption spectroscopic technique. An increased surface area for hollow morphology as compared to solid particles established a conspicuous boost in photocatalytic activity.
Keywords: excellent photocatalysis; synthesis; template free; ZnO hollow nanoparticles; ZnO-Ag nanocomposite

Short review of synthetic routes for the antiepileptic drug (R)-lacosamide - Aratikatla, Eswar K.; Bhattacharya, Asish K. (Organic Process Research & Development, 2020)
The disease epilepsy affects people of all ages and is due to a chronic neurological disorder in the brain. According to a report by the World Health Organization, epilepsy is one of the most common global neurological diseases. (R)-Lacosamide (Vimpat) was introduced by UCB Pharma in 2008 for the treatment of partial-onset seizures in patients suffering from epilepsy. This review summarizes all of the available synthetic strategies reported for (R)-lacosamide, which will help medicinal chemists in the further development of its synthesis.
Keywords: antiepileptic drug; epilepsy; lacosamide; serine derivative; synthesis

Synthesis and antimycobacterial screening of a novel series of alpha-amino acids containing thiazole linker - Nalawade, Jitendra L.; Mhaske, Pravin C.; Shinde, Abhijit D.; Chavan, Abhijit P.; Abhale, Yogita K.; Sarkar, Dhiman; Bobade, Vivek D. (ARKIVOC, 2022)
A small focused library of uncommon (S)-2-amino-3-(4-(((4-methyl-2-arylthiazol-5-yl)methyl)amino)phenyl) propanoic acid (5a-e) and (S)-2-amino-3-(4-(((2-arylthiazol-4-yl)methyl)amino)phenyl)propanoic acid (9a-d) derivatives have been efficiently synthesized by employing molecular simplification. The title compounds were screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis (BCG) strains. The cytotoxicity study was conducted against primary Human Umbilical Vein Endothelial Cells (HUVECs), on two different human tumor cells HeLa, and HCT 116 and was observed non-toxic to host cells.
Keywords: Amino acid; antibacterial activity; Cytotoxicity; Mycobacterium tuberculosis; synthesis; Thiazole

Short review on the synthetic routes for the antiepileptic drug (S)-levetiracetam - Paul, Sayantan; Bhattacharya, Asish K. (Organic Process Research and Development, 2024)
Epilepsy is a chronic disorder characterized by recurrent unpredictable seizures. Levetiracetam (Keppra) was introduced by UCB for the treatment of partial onset seizures in patients above 16 years of age diagnosed with epilepsy. This review reports synthetic strategies available for the synthesis of (S)-levetiracetam and will certainly aid the quest for the development of new routes for its synthesis.
Keywords: antiepileptic drug; butyrolactam; epilepsy; levetiracetam; synthesis